2012
DOI: 10.1111/j.1748-8583.2011.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

When partnerships don't ‘match‐up’: an evaluation of labour–management partnerships in the automotive components and civil aviation industries

Abstract: 60-75Following the agenda for partnership research set out recently in this journal, 'exemplar' case studies from the automotive and civil aviation industries are subject to the litmus (process) test of academic pluralists and the acid (outcomes) test of academic radicals. On both tests, the results have been disappointing, especially for trade unions and their members. However, while mutual gains from partnership agreements are not probable in a UK context, they are still possible, as comparative research in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…That the juxtaposition of the twin fatalities allied to a crisis of profitability served to “shock” the parties into an unprecedented coalition for change. Change initiatives, however, be they in non‐unionised or unionised settings are often “born out of crisis” (see, e.g., Evans et al's, study of Borg Warner) of one form or another again suggesting the findings have wider applicability.…”
Section: Limitationsmentioning
confidence: 91%
See 2 more Smart Citations
“…That the juxtaposition of the twin fatalities allied to a crisis of profitability served to “shock” the parties into an unprecedented coalition for change. Change initiatives, however, be they in non‐unionised or unionised settings are often “born out of crisis” (see, e.g., Evans et al's, study of Borg Warner) of one form or another again suggesting the findings have wider applicability.…”
Section: Limitationsmentioning
confidence: 91%
“…Although remaining “a moveable feast susceptible to redefinitions” (Ackers & Payne, , p. 546), standard formulations cite consensual managerial–labour relations (e.g., Johnstone et al, , p. 261), a commitment to mutual gains (e.g., Kochan & Osterman, ) and trust (Deitz, , p. 5), as core partnership principles. This format is often introduced in unionised settings as part of a broader set of change management and restructuring initiatives (e.g., Butler, Glover, & Tregaskis, ; Evans, Harvey, & Turnbull, ). For management, “the crucial side of this equation is flexibility” and ultimately business success (Terry, , p. 466).…”
Section: Organisational Change Workplace Partnership and Distributementioning
confidence: 99%
See 1 more Smart Citation
“…It is equally apparent that there is little consensus to the explanation about the waxing and waning of such collaborations and the various threads of this research agenda are likely to endure for some time (Wilkinson, Donaghey, Dundon and Freeman, in press). Many of the debates seeking to explain partnership success or failure over the past decade also approach the topic with an assessment of 'outcomes' as the holy grail, while others seek to understand the 'processes' that seek to deliver mutuality for the parties involved (Samuel 2007;Danford, Richardson, Stewart, Tailby and Upchurch 2008;Jenkins 2008;Johnstone, Wilkinson and Ackers 2009;Evans, Harvey and Turnbull 2012). The context is one in which radical changes in economic, market environments and industrial relations legislation are reshaping workplaces.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…Evans et al (2012) argue that both the process and outcomes of partnership must be examined in order to evaluate partnership. In terms of outcomes, Guest and Peccei (2001) demonstrated that both employers and workers on the whole witnessed gains from partnership, though employers benefited to a greater extent.…”
Section: Reconciling Interests: Mutual Gains and Pains Of Partnershipmentioning
confidence: 99%